Pelatihan Pembuatan Modul Pembelajaran Interaktif Berbasis Aplikasi Quizizz dan Google Slide bagi Guru SMAN 5 Parepare - Naili Suri Intizhami; Indar Chaerah Gunadin; Eka Qadri Nuranti; Putri Ayu Maharani; Mardhiyyah Rafrin; Muh Agus; Osama Iyad Al Ghozy; Nur Inaya Bahar; Muhammad Rivaldi Jefri; Muhammad Aldi Alfatih (Jurnal Pengabdian UNDIKMA, 2023)
This community service project aims to enhance the knowledge and skills of SMAN 5 Parepare teachers in developing interactive learning modules based on Google Slide and Quizizz applications and implementing Image Recognition technology. This method of implementation used training and reinforcement. This activity's evaluation instrument employed questionnaires, which were then descriptively analyzed using pre-test and post-test data. The results of this study indicated that teachers at SMAN 5 Parepare could develop interactive learning modules based on Google Slides and Quizizz adapted to the subject matter being taught. 38% of all questions answered correctly by the participants in this activity improved their teacher's skills.